Mitigation of nitrate leaching in tropical soils using layered double hydroxide - Kotlar, Ali Mehmandoost (2020)
Nitrate is the most intensively applied nutrient to agricultural land. Being a very mobile anion, even more in tropical acidic soils, its leaching easily contaminates surface and groundwater thus causing large financial loss for farmers. Estimation of water and solute fluxes using numerical models can be used to evaluate the efficiency of any hypothetical fertilizer management under a variety of soil and climatic conditions. As input, these models mainly require soil hydraulic properties, meteorological data and management scenarios. Therefore, the first objective of this study was to estimate soil hydraulic properties including water retention and hydraulic conductivity functions using easily measurable soil properties such as texture, organic matter or bulk density. Regarding nitrogen management practices, it is supposed that slow release fertilizers gradually release nitrate for root uptake leading to a reduction of nitrate loss, making them a good alternative to conventional fertilizers. This process was hypothetically modelled assuming application of slow-release fertilizers with different half-lives of 10, 20, 30 and 40 days under cultivation of summer maize and applying the commonly recommended 180 kg N ha-1. The yield of maize under application of SRFs with half-lives of 30 and 40 days showed to increase up to 200 kg N ha-1 and reduce leaching of nitrogen by 30 to 40 kg ha-1, unless bottom layers of the soil profile are very permeable. Finally, layered double hydroxides (LDH) which are supposed to be potentially applicable as slow release nitrate fertilizers were synthesized using a coprecipitation method and characterized by ICP-OES, XRD, FTIR and TGA analyses for nitrate release and leaching experiments. Batch experiments with LDH particles KCl, K2SO4 or CaCl2 showed that 60 to 100% of intercalated nitrate is exchanged by anions within a few hours. Soil column studies with soils from temperate (Denmark) and tropical (Brazil) regions confirmed rapid release of nitrate from LDH. Application of LDH to a soil profile with bulk density of 1300 kg m-3, 0.3 m rooting depth and a typical rate of field nitrogen application (120 kg ha-1) caused an accumulation of 400 to 1050 kg Mg and 230 to 478 kg of Fe or Al depending on type of LDH. This high load of residual metals and the relatively quick release of nitrate may restrain the use of the LDH as slow release nitrate source